Late induction of human DNA ligase I after UV-C irradiation. - Montecucco, A (1995)
We have studied the regulation of DNA ligase I gene expression in UV-C irradiated human primary fibroblasts. An increase of approximately 6-fold both in DNA ligase I messenger and activity levels was observed 24 h after UV treatment, when nucleotide excision repair (NER) is no longer operating. DNA ligase I induction is serum-independent and is controlled mainly by the steady-state level of its mRNA. The activation is a function of the UV dose and occurs at lower doses in cells showing UV hypersensitivity. No increase in replicative DNA polymerase alpha activity was found, indicating that UV induction of DNA ligase I occurs through a pathway that differs from the one causing activation of the replication machinery. These data suggest that DNA ligase I induction could be linked to the repair of DNA damage not removed by NER.